Entropy measures reveal collective tactical behaviours in volleyball teams: how variability and regularity in game actions influence competitive rankings and match status - Ramos, A.; Coutinho, P.; Silva, P.; Davids, K.; Guimarães, E.; Mesquita, I. (International Journal of Performance Analysis in Sport, 2017)
This study analysed and compared the influence of match status and final team rankings on variability of tactical performance behaviours within side-out phase, in female volleyball teams of different competitive levels. Performance data were analysed from matches (n = 8 for each level) in the 2012 Olympic women`s volleyball competition (elite level) and the Portuguese women`s league (national level) in the 2014-2015 season, with a total of 1496 rallies observed. Variability of setting conditions, attack zone, attack tempo and block opposition were assessed using Shannon entropy measures. Magnitude-based inferences were used to analyse and compare values of selected variables. Results showed that current match status had no influence on tactical performance of elite teams showing that they adapted their collective organisation without losing their game patterns. Analysis of final team rankings showed that, at national level, the highest ranked teams revealed greater unpredictability in all tactical performance measures (mainly in attack tempo and block opposition), emphasising the importance of the setter to differentiate performance of national teams. These findings may guide coaches in designing practice contexts for developing specific game patterns (setting conditions) and in seeking greater variability in other game actions (in attack), regardless of competitive level of performance.